The concept of śuddha tattvas in Śiva Śatakam by Nārāyaṇa Guruas a continuation and transformation of the Sanskrit and Tamiltraditions - Urbańska, Hanna (Gajt Wydawnictwo 1991 s.c., 2018)
In the present paper an attempt will be made toward interpreting selected stanzas from the work of Nārāyaṇa Guru (1854–1928), a South Indian philosopher and social reformer from Kerala. An analysis of the concept of śuddha tattvas presented by Guru in his several Malayalam works, among others Śiva Śatakam („Hundred Verses Devoted to Śivan”), Svānubhava Gīti („Lyric of Ecstatic Self-Experience”) as well as Ᾱtmōpadēsa Śatakam („Hundred Verses on Self-Instruction”) in the light of S anskrit and Tamil literary sources shows clearly that Guru’s philosophical works could have been influenced by Laya Yoga (Kuṇḍalinī Yoga) system as well as by Tamil Śaiva Siddhānta; Nārāyaṇan seems to apply the Tamil style of presentation of yogic experiences while introducing the twilight language to his works, at the same time proving his proficiency in Sanskrit language and literature.
Keywords: Śaivism,; Śiva Śatakam; Tirumantiram; Nārāyaṇa Guru; śuddha tattva